Quantification of class 1 integrons and characterization of the associated gene cassettes in the high Arctic – Interplay of humans and glaciers in shaping the aquatic resistome - Nicoletta Makowska-Zawierucha; Joanna Mokracka; Marcelina Małecka; Piotr Balazy; Maciej Chełchowski; Dariusz Ignatiuk; Krzysztof Zawierucha (Ecological Indicators, 2022)
The Arctic is one of the regions most affected by global climate change, and is subjected to changes linked with a melting cryosphere and increasing anthropopressure. Although antibiotic resistance is a global problem, the diversity and spread of antibiotic-resistant bacteria (ARB), antibiotic resistance genes (ARGs) and integrons in the Arctic are strongly understudied. Therefore, the main aims of this study are the (1) determination of the type and frequency of integron-integrase genes and characterization of incorporated gene cassettes in the genomes of culturable bacteria and (2) quantitative analysis of class 1 integron-integrase gene and human mitochondrial DNA (Hmt-DNA) in the metagenome as markers of anthropogenic impact on the high Arctic environments of the Svalbard Archipelago. Samples of ice, water and sediments were collected in the most populated area of Svalbard, Longyearbyen and its vicinity. Sampling was conducted along an environmental gradient with varying levels of human activity. The environmental gradient started from glaciers, following the proglacial river, the seashore, and the fjord bottom water, including untreated wastewater outflow to the sea. Class 1 integrons were detected in ARB isolated from glacial environments, freshwater and seawater, including wastewater outflow. Moreover, in the variable regions of integrons, genes determining different functions, including antibiotic resistance, virulence and physiological traits were found. These genes play crucial roles in the adaptation of bacteria to cold and dynamic environments. The relative abundance of intI1 genes were reported in metagenomes with different relationships to human activity (ice cores vs wastewater outflow), with the highest mean values observed in the wastewater outflow, and was positively correlated with abundance of the Hmt gene, revealing both natural and human roles in shaping the polar aquatic resistome.